Development of Flux for Lead free Soldering of High Power Devices - SUN Feng-lian; PENG Li-juan (Journal of Harbin University of Science and Technology)
Halogen-free low-Rosin flux was applied to lead-free soldering of the high-power devices with orthogonal test method. The compositions of flux such as active agent, solvents, film-forming agent were optimized and the spreading rate, corrosion resistance and physical properties of the flux were texted, according to GB/T 31474-2015 soldering fluxes for high-quality interconnections in electronic assembly. The results showed that: the new flux has good physical stability and wettability, and the highest average rate of expansion is 86%, when mass fraction of organic acid active agent is 15%, rosin mass fraction is 30% and thixotropic agent is 1% in the flux. The corrosion of residues after reflow is little to the copper plate, and the new flux well meets the requirements of the electronic device.